MEOP-CTD in-situ data collection: a Southern ocean Marine-mammals calibrated sea water temperatures and salinities observations ... - Roquet, Fabien; Guinet, Christophe; Charrassin, Jean-Benoit; Costa, Daniel P.; Kovacs, Kit M; Lydersen, Christian; Bornemann, Horst; Bester, Marthan N.; Muelbert, Monica C.; Hindell, Mark A.; McMahon, Clive R.; Harcourt, Rob; et al. (SEANOE, 2024)
The Southern Ocean plays a fundamental role in regulating the global climate. This ocean also contains a rich and highly productive ecosystem, potentially vulnerable to climate change. Very large national and international efforts are directed towards the modeling of physical oceanographic processes to predict the response of the Southern Ocean to global climate change and the role played by the large-scale ocean climate processes. However, these modeling efforts are greatly limited by the lack of in situ measurements, especially at high latitudes and during winter months. The standard data that are needed to study ocean circulation are vertical profiles of temperature and salinity, from which we can deduce the density of seawater. These are collected with CTD (Conductivity-Temperature-Depth) sensors that are usually deployed on research vessels or, more recently, on autonomous Argo profilers. The use of conventional research vessels to collect these data is very expensive, and does not guarantee access to ...